2017
DOI: 10.1038/s41598-017-13101-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light, gibberellic acid and nitrogen source on germination of eight taxa from dissapearing European temperate forest, Potentillo albae-Quercetum

Abstract: Little is known about how light affects seed germination and revegetation of species of thermophilous oak forest. To reveal this relationship effects of white, red, far-red irradiations and dark incubation on germination of eight Potentillo albae-Quercetum taxa were examined. Attempts were also made to evaluate the influence of gibberellic acid and different nitrogen sources on the germination characteristics. Interaction between light and nitrogen was also studied. Freshly matured seeds of all taxa germinated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 45 publications
2
13
0
Order By: Relevance
“…Podzols). Similar conclusion was drawn regarding some woodland species from Spain [ 14 ] and some species from temperate thermophilous oak forest [ 40 ]. Only a few of the species we studied ( C .…”
Section: Discussionsupporting
confidence: 80%
“…Podzols). Similar conclusion was drawn regarding some woodland species from Spain [ 14 ] and some species from temperate thermophilous oak forest [ 40 ]. Only a few of the species we studied ( C .…”
Section: Discussionsupporting
confidence: 80%
“…In our study, the mean FGP of all species showed a hump-shaped pattern for the focal species. The optimal concentration of the nitrogenous solutions for germination was 10 mM, whereas higher concentrations had a lower effect (Kolodziejek et al, 2017). We found that low nitrogen concentration promoted seed germination, such as for P. bifurca, P. asiatica, and S. viridis, with no negative effect under high nitrogen concentrations.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, previous studies have reported that light competition is a major driver of species loss following nutrient enrichment (DeMalach, Zaady, & Kadmon, 2017;Grace et al, 2016;Harpole & Tilman, 2007). The amount of light affecting the undergrowth is a principal condition controlling seed germination and seedling survival (Kolodziejek, Patykowski, & Wala, 2017). An experiment to explore the effects of the amount of light on seeds from different functional groups should be performed in the future.…”
Section: Seedling Diversity Response To N Additionmentioning
confidence: 99%